Electrospinning and Catalytic Properties of Cyclodextrin Functionalized Polyoxymethylene (POM) Nanofibers Supported by Silver Nanoparticles - C. Q. Zhang (Hindawi-Wiley, 2021)
A series of novel composite microfibers composed of β-cyclodextrin (β-CDs) functionalized POM (polyoxymethylene) were prepared using electrospining technology with a mixture of hexafluoroisopropanol (HFIP) and N,N-dimethylformamide (DMF) as solvent. The concentration of β-CDs with respect to the POM was varied from 0 to 50 wt.%. The effect of β-CDs content on the morphology of POM/β-CD composite microfiber was investigated. The results showed that the introduction of β-CDs reduced the surface roughness and porosity of the microfibers, and the morphology of the fibers was changed. The increase of β-CDs content from 10% to 50% has led to increased average diameter of POM/β-CD composite fiber from 2.1 μm to 6.4 μm. The mechanical properties of the blend fiber mats were further investigated. In addition, silver nanoparticles were introduced to the POM/β-CD composite microfiber matrices during electrospinning. The POM/β-CD composite fiber allows CDs to form host–guest complexes with various small molecules and macromolecules. The TEM, SEM, XRD, and XPS were utilized to characterize the prepared samples. The data suggest that Ag nanoparticles were homogeneously distributed within the POM/β-CD fibers, and no aggregation was observed. The catalytic activity of Ag nanoparticles was tracked by ultraviolet-visible (UV-vis) spectroscopy which showed excellent catalytic degradation performance of organic dyes in the presence of NaBH4. The Ag/POM/β-CD mats are promising for use in waste treatment, molecular recognition, catalysis, and so on.